(untitled) (Social and Environmental Law Journal, 2024)
ARBEX, Daniela. Holocausto Brasileiro. São Paulo: Geração Editorial, 2013. Daniela Arbex is a Brazilian journalist and documentarian. She graduated in 1995 with a degree in Social Communication from the Federal University of Juiz de Fora, beginning her career at the newspaper Tribuna de Minas, where she served as a special reporter for over two decades. Dedicated to the defense of human rights, Arbex has been recognized for her work as an investigative journalist. As the author of Holocausto Brasileiro, she received the Best Reportage Book of the Year award from the São Paulo Association of Art Critics (2013) and the second place for Reportage Book at the Jabuti Prize (2014), with over 300,000 copies sold in Brazil and around the world. Espanhol: